The Impact Mechanism of Post-Pandemic Financial Policy on Fluctuations in Housing Price in China’s First-tier Cities - Chen Limingxu (SHS Web of Conferences)
The COVID-19 epidemic has had a profound impact on China’s real estate market, especially the significant fluctuations in housing prices in first-tier cities. The government has adopted a series of financial policies, such as lowering the loan prime rate (LPR), adjusting credit quotas, and implementing monetary easing, to ease market pressure and stimulate demand. However, there are differences in the response of housing prices in different cities to financial policies. Beijing’s housing prices are relatively sluggish, while Shenzhen and Guangzhou’s markets have recovered rapidly. This study uses VAR models and time series analysis methods to explore the dynamic impact of financial policies on housing prices in first-tier cities, and combines panel data to analyse the heterogeneous responses of different cities. The results reveal the role of financial policies in stabilizing the real estate market but also reflect the complexity and limitations of policy intervention. The study not only helps to understand the interactive relationship between financial policies and the real estate market under the impact of the epidemic but also provides empirical support for the government to optimize the housing market regulation strategy.